Diseño de un modelo de gestión de calidad para mejorar el servicio y la productividad en la Oficina de Adquisiciones del Hospital IV - Víctor Lazarte Echegaray de Trujillo. - Silencio Miñano, David Williams (2012)
The design of a model of quality management to improve service and productivity in the Office of procurement of Hospital IV - Victor lazarte Echegaray of Trujillo, in these times, takes vital by the current need to handle management, such as the quality and the productivity tools that will help identify gaps that exist between the desired and the actual situation, and on this basis to build appropriate mechanisms for the achievement of institutional objectives, on the basis of the subject of our study Office is the axis on which moves the functioning of Hospital IV - Victor Lazarte Echegaray of Trujillo, to be responsible for organizing, driving and controlling system of procurement, warehouse, and contracting of goods and services; as well as directing and controlling processes of reception, physical location, conservation, inventory control and supply of goods in the warehouse of the healthcare network. Likewise, it is important to recognize that the process of quality management does not work by itself alone, but that this is an instrument that will allow to determine how efficient and effective are still employees in the work assigned, in order to achieve the goals, mission and drawn vision, is being searched initially to determine gaps that exist in the enterprise and on this basis develop or complement the areas and improvement processes.